A Study Of English Songs On Teaching Vocabulary At Kindergaten Students Of Lembaga Pendidikan Islam Bustanuddin Galis Pamekasan - Ratnawati, Rinta; Wafi, Abdul; Navlia, Rusdiana (Institut Agama Islam Negeri Madura, 2020)
Teaching English to young learners, especially for kindergarten students, is focused on teaching vocabulary because they are still introduced to new language in which it has not ever been learned before. The use of songs in teaching vocabulary for young learners is an effective way to teach English. This study is descriptive qualitative research because (1) It is concerned with context and meaning, (2) the researcher works in natural setting, (3) the researcher is the key instrument in collecting data, (4) the data are presented descriptively, and (5) the data are analyzed inductively. The subjects are kindergarten students and the English teacher. In this study, the instruments used are observation checklist, field note, and interview guide for the four teachers. From the findings, it can be concluded the characteristics of the songs used in teaching vocabulary were the lyrics of the songs were simple and not too long, there was the repetition of the words while singing the songs, the vocabulary used in the lyrics was presented in the meaningful context, the lyrics were based on the theme in the school curriculum, and the rhythm of the songs was fun, The teachers also considered the criteria of the appropriate songs for their students while they were selecting the songs.